Performance of Tawangsari Health Center, Sukoharjo Regency Reviewed from Motivation, Workload, Environment and Occupational Safety and Health (K3) - Andriyansyah, Nova; Istiatin, Istiatin; Sudarwati, Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of work motivation, workload, work environment, and occupational safety and health (K3) on the performance of employees of the Tawangsari Health Center, Sukoharjo Regency, both simultaneously and partially. This research method uses a quantitative approach with a descriptive research design. The population of the study was all employees working at the Tawangsari Health Center, Sukoharjo Regency, with a sampling technique using the census method, so that the number of research samples was 89 employees. Data collection was carried out through questionnaires. Data analysis techniques used include multiple linear regression tests, F tests, t tests, and coefficients of determination. The results of the study showed that partially and simultaneously, the variables of work motivation, workload, work environment, and occupational safety and health (K3) had a significant effect on the performance of employees of the Tawangsari Health Center, Sukoharjo Regency. Therefore, the management of the Health Center is advised to increase employee work motivation through awards and training, adjust the workload to be more proportional, create a comfortable and conducive work environment, and strengthen the implementation of occupational safety and health programs in order to improve employee performance optimally.